Iron‐Catalyzed Generation of α‐Amino Nitriles from Tertiary Amines. Issue 14 (2nd October 2013) - Wagner, Alexander; Han, Wei; Mayer, Peter; Ofial, Armin R.
Abstract The use of iron(II) chloride as catalyst, trimethylsilyl cyanide as source of cyanide ions, and tert‐butyl hydroperoxide as oxidant enabled the conversion of aromatic, benzylic, and aliphatic tertiary amines into α‐amino nitriles under mild conditions. Chemoselective functionalization of NCH3 to NCH2CN was achieved in the presence of N‐benzyl and N‐alkyl groups. N, N‐Dialkylanilines, PhNR2, with R=Et, Bu, Bn furnished the alkyl(aryl)aminoacetonitriles PhN(R)CH2CN as the main products accompanied by α‐amino nitriles generated by ordinary α‐cyanation of the aniline PhNR2. Formation of PhN(R)CH2CN was rationalized by oxidative degradation of N, N‐dialkylanilines to N‐alkylanilines, their condensation with formaldehyde, generated by oxidation of the solvent methanol, and final trapping of the thus formed iminium ions by cyanide. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>